Utilidad de las técnicas nucleares en nutrición: Evaluación de la masa grasa corporal y de la ingesta de leche materna - Pallaro, Anabel (2014)
The application of nuclear techniques in the area of nutrition is safe because they use stable isotopes. The deuterium dilution method is used in body composition and human milk intake analysis. It is a reference method for body fat and validates inexpensive tools because of its accuracy, simplicity of application in individuals and population and the background of its usefulness in adults and children as an evaluation tool in clinical and health programs. It is a non-invasive technique as it uses saliva, which facilitates the assessment in pediatric populations. Changes in body fat are associated with non-communicable diseases; moreover, normal weight individuals with high fat deposition were reported. Furthermore, this technique is the only accurate way to determine whether infants are exclusively breast-fed and validate conventional methods based on surveys to mothers.